2020
DOI: 10.1007/s00262-020-02607-7
|View full text |Cite
|
Sign up to set email alerts
|

A TLR4–TRIF-dependent signaling pathway is required for protective natural tumor-reactive IgM production by B1 cells

Abstract: Metastatic cancer involving spread to the peritoneal cavity is referred to as peritoneal carcinomatosis and has a very poor prognosis. Our previous studies demonstrated a toll-like receptor 4 (TLR4) and C-type lectin receptor (CLR; Mincle/MCL) agonist pairing of monophosphoryl lipid A (MPL) and trehalose-6,6'-dicorynomycolate (TDCM) effectively inhibits peritoneal tumor growth and ascites development through a mechanism dependent upon B-1a cellproduced natural IgM, complement, and phagocytes. In the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“… 15 , 16 These series of reactions invoke immune cell infiltration 6 and activation. 17 In addition, Mincle −/− bone marrow-derived cells lose their ability in dynamic balance of pro- and anti-inflammatory cytokines, which affects cytotoxicity CD4 + T cell function such as interferon (IFN)-γ production. 18 Glycolipid-stimulated M1 polarization is another important immunomodulation in phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 These series of reactions invoke immune cell infiltration 6 and activation. 17 In addition, Mincle −/− bone marrow-derived cells lose their ability in dynamic balance of pro- and anti-inflammatory cytokines, which affects cytotoxicity CD4 + T cell function such as interferon (IFN)-γ production. 18 Glycolipid-stimulated M1 polarization is another important immunomodulation in phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TLR4 expressed by B cells was shown to be key in early IgM production in mice, which is partially able to counteract Leptospira infection ( 4 ). We may speculate that early IgM production, activated three days post infection, may be linked to a role of TLR4, as it was recently shown that B1 cell activation and tumor-reactive IgM production were defective in TLR4 KO mice ( 25 ).…”
Section: Discussionmentioning
confidence: 92%
“…For example, TLR4 expressed by B cells was shown to be key in early IgM production in mice, which is partially able to counteract Leptospira infection [4]. We may speculate that early IgM production, activated three days post infection, may be linked to a role of TLR4, as it was recently shown that B1 cell activation and tumor-reactive IgM production were defective in TLR4 KO mice [21].…”
Section: Discussionmentioning
confidence: 95%